Implementasi Kebijakan Ruang Terbuka Hijau (RTH) Di Taman Kota Giri Menang: Implementation Of the Green Open Space (RTH) Policy at Giri Menang City Park - Windiati, Windiati; Ichsan, Andi Chairil; Aji, Irwan Mahakam Lesmono (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2024)
Green Open Space can be interpreted as a space that maximises the length of the path or what is called a grove. Green open space serves to balance the ecological conditions in an area so that there is a balance between the ecosystem and the development of development in the modern era. In line with this, the government also regulates RTH and makes regulations contained in a regulation and implements programmes aimed at fulfilling the proportion of RTH in the Regency / City, especially in Green Open Space (RTH) as a support for community comfort. Based on Law Number 26 of 2007 concerning Spatial Planning mandates that each city must have a minimum Green Open Space (RTH) of 30%, where the city area must be in the form of RTH consisting of 20% public RTH and 10% private RTH. This research aims to find out, describe, and analyse the implementation of the green open space arrangement policy in Giri Menang City Park. This research was conducted in Giri Menang City Park, Gerung District, West Lombok Regency, West Nusa Tenggara. This research uses purposive sampling technique for determining respondents and snowball sampling for selecting respondents. The variables used here are based on William N Dunn's theory and analysed using qualitative and quantitative analysis. The results showed that the policy implementation of the Giri Menang City Park was reviewed based on William Dunn's theory using 6 criteria, namely effectiveness, efficiency, adequacy and responsiveness, which were included in the high category while equity and accuracy were in the medium category.